Clinical Improvement of Bullous Pemphigoid with Hyperkeratosis and Palmoplantar Keratoderma in Two Patients Treated with Dupilumab - Giulia Pascolini; Feliciana Mariotti; Anna Pira; Biagio Didona; Giovanni Di Zenzo (Medical Journals Sweden, 2024)
Abstract missing (Short communication)